THE INFLUENCE OF FAST FASHION AND VISUAL SOCIAL MEDIA ON STUDENTS' CONSUMER BEHAVIOR : A HIRARCHICAL MULTIPLE REGESSION STUDY - Inas Amatullah; Didik Nurhadi; Nurul Hidayati; Sriwahyuningsi Hammar (SOSIOEDUKASI, 2026)
The development of visual social media has changed the way students access information and consume fashion products. For fashion students, social media is not only used for personal interests, but also as a learning medium to keep up with fashion developments. This duality of functions then blurs the line between academic needs and consumption of fashion products, making them a vulnerable group to the urge to consume fashion products, especially fast fashion products. This study aims to examine the influence of fast fashion, Instagram, and Pinterest in influencing the consumer behavior of fashion products among students. This research is explanatory with a quantitative approach. The population of this study is Bachelor of Fashion Design Education and Bachelor of Applied Fashion Design students at the State University of Malang, with a total sample of 160 respondents taken through purposive random sampling technique. Data were collected using a questionnaire and analyzed using hierarchical multiple regression analysis techniques. The results show that, overall, the three variables together explain with R2 of 20.6% of the variation in students’ consumption behavior. Specifically, fast fashion is the dominant predictor, exerting a significant positive influence with a standard beta of 0.289. The inclusion of the Instagram variable also exerts a significant influence due to several factors, such as the FoMO phenomenon. Conversely, the inclusion of the Pinterest variable actually had a significant negative effect on consumer behavior. This suggests that Pinterest serves more as a source of inspiration for creative ideas and academic design than directly encouraging impulsive purchases among students.